Scoliosis instrumentation alters primary and coupled motions of the spine: An in vitro study using entire thoracolumbar spine and rib cage specimens - Christian Liebsch; Peter Obid; Morten Vogt; Benedikt Schlager; Hans‐Joachim Wilke (JOR Spine)
Abstract Background Effects of rigid posterior instrumentation on the three‐dimensional post‐operative spinal flexibility are widely unknown. Purpose of this in vitro study was to quantify these effects for characteristic adolescent idiopathic scoliosis instrumentations. Methods Six fresh frozen human thoracic and lumbar spine specimens (C7‐S) with entire rib cage from young adult donors (26–45 years) without clinically relevant deformity were loaded quasi‐statically with pure moments of 5 Nm in flexion/extension, lateral bending, and axial rotation. Primary and coupled motions of all segments were measured using optical motion tracking. Specimens were tested without instrumentation and with posterior rod instrumentations ranging from T2 to L1 (for Lenke Type 2) and from T8 to L3 (for Lenke Type 5) based on survey results among spinal deformity surgeons. Statistical differences were evaluated using the pairwise Friedman test. Results Primary ranges of motion were significantly (p < 0.05) reduced in all six motion directions in the entire thoracic spine (T1‐L1) for both instrumentations, but solely in extension and axial rotation in the entire lumbar spine (L1‐S) for T8‐L3 instrumentation. Without instrumentation, strong ipsilateral axial rotation during primary lateral bending and strong contralateral lateral bending during primary axial rotation were detected in the thoracic spine (T1‐L1) and slight inverse coupled motions in the lumbar spine (L1‐S). While coupled axial rotation was significantly (p < 0.05) reduced, especially in the upper thoracic spine (T1‐T5) for T2‐L1 instrumentation and in the lumbar spine (L1‐S) for T8‐L3 instrumentation, coupled lateral bending was solely significantly (p < 0.05) reduced in the upper thoracic spine (T1‐T5) for T2‐L1 instrumentation. Coupled motions in primary flexion and extension were non‐existent and not affected by any fixation (p > 0.05). Conclusions Instrumentation reduces the primary flexibility and diminishes the natural coupling behavior between lateral bending and axial rotation, primarily in the upper thoracic spine, potentially causing correction loss and junctional deformity in the long‐term.